Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pasien dengan Halusinasi - Nani, Mohamad Iswanto; Fani, Rif'atul; Cahyaningrum, Putri (Pustaka Galeri Mandiri, 2026)
Schizophrenia with hallucinations is a chronic mental disorder that requires long-term treatment, but medication non-compliance remains a major problem, increasing the risk of relapse. In primary healthcare, family support plays a crucial role as the closest support system influencing patient adherence. This study aims to analyze the relationship between family support and medication adherence in patients with hallucinations undergoing outpatient care at the Suwawa Community Health Center, Bone Bolango, Gorontalo. The study used a quantitative approach with a cross-sectional correlational design. A sample of 30 respondents was selected using a convenience sampling technique. Data were collected through a structured questionnaire and analyzed using the Spearman Rank correlation test. The results showed a significant and positive relationship between family support and medication adherence, with a p-value of 0.009 and a correlation coefficient of r-value of 0.471, indicating a moderate relationship. These findings emphasize the importance of the family's role in improving medication adherence in patients with mental disorders in primary healthcare